Antiarrhythmic therapy effects on quality of life among patients with extrasystoles - V. L. Doshchitsyn; O. A. Kramynina; E. V. Chernova; O. B. Karpunichev; O. V. Barysheva; E. Yu. Shatykhina; Yu. V. Bezborodova (Российский кардиологический журнал, 2008)
To investigate antiarrhythmic therapy effectiveness, safety and impact on quality of life (QoL) among patients with symptomatic extrasystolia, a study was performed in 152 individuals, with 140 completing the study. Mean age of the patients was 57 years; 102 patients sufferedfrom chronic coronary heart disease (CHD), 33 - from Grade IIessential arterial hypertension (AH) without CHD. Therapy included propafenone (Propanorm, PRO/ MED.CS Praha a.s.) in the dose of 300-450 mg/d, amiodarone (Cordaron, SANOFIWINTHROPINDUSTRIE), in the initial dose of 600 mg/d, gradually reduced to 200 mg/d, and metoprolol (Egilok, EGIS PHARMACEUTICAL Ltd.) in the dose of 50-100 mg/d. The treatment started in the hospital, followed by out-patient therapy. The follow-up period varied from 12 to 24 months, with mean duration of 18 months. If clinical course improved, antiarrhythmic therapy (AAT) could be stopped, starting again in case of recurrent extrasys-tolia. AAT effectiveness was assessed by Holter ECG monitoring, QoL - by special questionnaires. Assessment took place at baseline, as well as 10-21 days and 12 months after the therapy start. In general, AAT was well tolerated. AAT discontinuation due to adverse effects took place in 11,4 %, 9,5%, and 6,1 % of those receiving amiodarone, propafenone, and metoprolol, respectively. AAT with propafenone, amiodarone and metoprolol was associated with reduction in the extrasystolia number by ≥70 %, 62 %, and 38,2 %, respectively. It was also associated with QoL improvement and reduced anxiety and depression. These changes were maximal and reaching statistical significance in those receiving propafenone and amiodarone, comparing to the metoprolol group. QoL improvement correlated with reduction in extrasystolia number. Therefore, AAT with propafenone, amiodarone, and to a lesser extent, metoprolol, improved QoL in patients with subjective arrhythmia symptoms. The magnitude of this effect depended on antiarrhythmic effectiveness of the medications used. Long-term AAT, in particular, with propafenone and amiodarone, was safe, including patients with chronic CHD.